WEWENANG INSPEKTORAT PENGAWASAN DAERAH POLDA DALAM PENCEGAHAN TINDAK PIDANA KORUPSI DI KEPOLISIAN DAERAH SULAWESI TENGAH AUTHOR INSPECTORATE AUTHORITORS FOR PREVENTION OF CRIMINAL ACTIONS IN CORRUPTION IN REGIONAL SUPPORT CENTRAL SULAWESI - Hamzah, Amir (Universitas Tadulako, 2020)
This study aims to find out and analyze the authority of the Central Sulawesi Regional Police Supervisory Inspectorate (Itwasda), with the aim of knowing and analyzing the prevention of Corruption Crimes. The type and type of this research is normative juridical by conducting literature searches, and police regulations related to the authority of the Regional Supervision Inspectorate (Itwasda) in supervision and inspection. Republic of Indonesia National Police Chief Regulation Number 22 of 2010 concerning Police Organizational Structure and Work Procedures at the Regional Level (Polda) which is the main reference in answering the problems of Supervision and Inspection in the work area of the Central Sulawesi Regional Police. The results of the discussion that based on Perkap 22 of 2010 there is no mention that the Regional Supervision Inspectorate (Itwasda) is a Work Unit that serves to prevent corruption, but in the implementation of activities other than the assistant leader of the Regional Supervision Inspectorate (Itwasda) has the main task of Supervision and Examination in the fields of Operations, Human Resources (HR), Infrastructure and Statements. The activity was carried out in two phases: the first and the second stages, the first stage included aspects of planning and organizing, stage two included aspects of implementation and control. The results of the implementation and inspection will be reported to the Leader for the nextÂ